Virtual Reality Applications for Neurological Disease: A Review - Schiza, Eirini; Matsangidou, Maria; Neokleous, Kleanthis; Pattichis, Constantinos S. (Frontiers in Robotics and AI, 2019)
Recent advancements in Virtual Reality (VR) immersive technologies provide new tools for the development of novel and promising applications for neurological rehabilitation. The purpose of this paper is to review the emerging VR applications developed for the evaluation and treatment of patients with neurological diseases. We start by discussing the impact of novel VR tasks that encourage and facilitate the patient's empowerment and involvement in the rehabilitation process. Then, a systematic review was carried out on six well known electronic libraries using the terms: ‘Virtual Reality AND Neurorehabilitation’, or ‘Head Mounted Display AND Neurorehabilitation’. This review focused on fully-immersive VR systems for which 12 relevant studies published in the time span of the last five years (from 2014 to 2019) were identified. Overall, this review paper examined the use of VR in certain neurological conditions such as dementia, stroke, spinal cord injury, parkinson’s and multiple sclerosis. Most of the studies reveal positive results suggesting that VR is a feasible and effective tool in the treatment of neurological disorders. In addition, the finding of this systematic literature review suggested that low-cost, immersive VR technologies can prove to be effective for clinical rehabilitation in healthcare and home-based setting with practical implications and uses. The development of VR technologies in recent years has resulted in more accessible and affordable solutions that can still provide promising results. Concluding, VR and interactive devices resulted in the development of holistic, portable, accessible and usable systems for certain neurological disease interventions. It is expected that emerging VR technologies and tools will further facilitate the development of state of the art applications in the future, exerting a significant impact on the wellbeing of the patient.